How Seo Influences Editorial Decisions In Detikcom’s News Production - Akmalia, Shobihatunnisa; Herawati, Maimon; Aunillah, Rinda (Universitas 17 Agustus 1945 Surabaya, 2024)
The shift in news production processes, which now places greater emphasis on audience interests, has compelled online news media to consider a strategic position in search engines. Consequently, the utilization of Search Engine Optimization (SEO) by online news media is crucial, with Detikcom being one prominent example. Detikcom has successfully leveraged digital platforms to capture audience attention, securing the top position as the most visited online mass media in Indonesia. Therefore, this study aims to examine how Detikcom utilizes SEO in the news production process. The research will explore how SEO is integrated into Detikcom's editorial considerations during news production. This study employs a descriptive research method with a qualitative approach. The findings indicate several factors influencing the editorial team's consideration of SEO in the news production process. First, the extent to which SEO supports the editorial team in news production is evaluated. In practice, SEO is closely intertwined with the daily routines of Detikcom's editorial team when producing news. Second, SEO can be used as a strategy to reach a broader audience. The use of SEO is considered effective in attracting new audiences and increasing website traffic. Third, the implementation of SEO is done to compete with competitors. This involves analyzing the SEO strategies of competitors, as reflected in the content they produce. Fourth, the varying cultures within each channel result in different approaches to SEO implementation across channels. This correlates with the routines and policies applied within each channel and how each channel perceives the importance of SEO. Keywords: Search Engine Optimization, editorial policy, news production, qualitative descriptive studies